Internalisasi Nilai Moderasi Islam Melalui Pengembangan Kurikulum Muatan Lokal Aswaja An-Nahdliyah di MTs Raudlatut Thalabah Kediri - Akbar, Akbar Muharom; Fiddini, Irva Aghnia; Nurfalah, Yasin (Indonesian Proceedings and Annual Conference of Islamic Education (IPACIE), 2022)
Educational institutions as a learning environment function in shaping the pattern of life and character of society. Through learning activities as the core of the education process, internalization of Islamic moderation values must be implemented in order to become a strong character for learners. Through the development of the local content curriculum Aswaja An-Nahdliyah with Aswaja and Ke-NU-an subject matter that stands alone MTs Raudlatut Thalabah Kediri seeks in internalizing the value of Islamic moderation with guidance provided by LP Ma'arif. So the purpose of this research is to find out the process of developing the local content curriculum of Aswaja An-Nahdliyah and how to internalize the value of Islamic moderation through the local content curriculum Aswaja An-Nahdliyah. The research method used is a qualitative method with a case study approach. The result of the research is the development of a local content curriculum using a bottom up strategy, the school is assisted by regional administrator LP Ma'arif to determine the type and material of the local content study, through the identification stage, determination of local load type and implementation. The process of internalization through the delivery of Aswaja and Ke-NU-an subject matter, habituation and motivation programs. Keywords: Aswaja An-Nadhliyah, Local Content Curriculum, Islamic Moderation